Health provider perspectives on differentiated service delivery for HIV in Oyo state, Nigeria: exploring the experiences of service providers from a demand perspective - Adelaja Modupe Gift; Folahanmi Tomiwa Akinsolu; Olunike Rebecca Abodunrin; Akim Tafadzwa Lukwa; Mobolaji Timothy Olagunju; Adekemi Akinpelu; Ogunwale Mercy Mary; Ola Oluwabukola Mary; Dolapo Omotayo Raji; Lilian Ogochukwu Ezechi; Aisha Oluwaseun Gambari; Oliver Chukwujekwu Ezechi (BMC Health Services Research)
Abstract Background Differentiated Service Delivery (DSD) models have been introduced to optimise HIV care by adapting services to client needs while reducing the burden on healthcare systems. In Nigeria, where HIV prevalence remains high. Understanding provider perspectives is critical to improving and sustaining DSD implementation. This study explored the experiences, challenges, and recommendations of healthcare providers involved in DSD delivery in Ibadan North, Oyo State. Methods A qualitative descriptive study was conducted between July and September 2024, involving 11 key informant interviews and two focus group discussions across three DSD-implementing facilities. Participants included clinicians, ART counsellors, HTS providers, retention officers, and program managers. Data were analysed thematically using NVivo 12 software, following the Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines. Results Five core themes emerged: perceived benefits of DSD models, implementation challenges, eligibility and suitability of clients, human resource capacity and training, and strategic recommendations for sustainability. Providers reported that DSD models improved accessibility, reduced clinic congestion, and enhanced patient retention and viral suppression. However, challenges such as inaccurate client data, dependency on community models, systemic inefficiencies, and inadequate training impeded effective implementation. Participants emphasised the need for policy alignment, community engagement, capacity building, and stronger monitoring systems. Conclusion DSD models hold promise for improving HIV service delivery in Nigeria. However, their success depends on addressing structural and operational challenges, tailoring approaches to local contexts, and strengthening health workforce capacity. These findings provide critical insights to inform national policy, support program scale-up, and contribute to achieving the UNAIDS 95-95-95 and SDG 3.3 targets.